MEANS OF ACTIVATING EDUCATIONAL ACTIVITIES OF FUTURE MATHEMATICS TEACHERS DURING THE STUDY OF MATHEMATICAL ANALYSIS - Boiaryshcheva, Tetiana; Herych, Myroslava; Pohoriliak, Oleksandr; Syniavska, Olga; Tegza, Antonina (Physical and Mathematical Education, 2022)
Formulation of the problem. The primary task of the higher education system is the training of highly qualified specialists in various fields of science and production. At the same time, the education system itself is forced to organize its activities in extreme conditions. The sharp transition to distance learning primarily deprived teachers and students of education of live communication, which caused a weakening of cognitive activity. The consequence of this, in turn, was that the knowledge acquired unwillingly is vague and superficial. Therefore, identifying and researching means that would stimulate the cognitive activity of the acquirer is one of the primary tasks of the education system. Instead, the transition to distance learning has forced teachers to make extensive use of computer-based learning tools, in particular, a variety of programs and applications that have an unlimited range of possibilities in the study of mathematics. The practical significance of these means is extremely great. Along with their application according to their immediate purpose, they also encourage the practical application of acquired theoretical knowledge; stimulate the assimilation of new forms and methods of learning, which is especially important for a future teacher. At the same time, it is necessary to maintain a balance in the issue of using these funds. After all, they are not able to independently form a complete system of knowledge in a student and are only an auxiliary, albeit very effective, tool. Research and comparison of some of these programs' capabilities and traditional teaching methods are the subjects of this article.Materials and methods. In the research process, theoretical (analysis of educational and methodological literature, comparative analysis of capabilities of the GeoGebra environment and the Maxima package) and practical research methods were used (study of the effectiveness of various classic methods of solving problems, consideration of the functional capabilities of the GeoGebra and Maxima services for effective learning of the material in the learning process mathematical analysis).Results. In this article, to activate the cognitive activity of the student during the study of mathematical analysis, it is proposed to combine classical tools with modern computer tools, in particular, the use of GeoGebra and Maxima packages. The implementation of this approach is shown in concrete examples.Conclusions. Activation of the cognitive activity of students of higher education is achieved, in particular, by increasing the level of educational motivation, which is observed when the learning process is as close as possible to students' individual aspirations and capabilities. Helps to activate cognitive activity in the process of studying mathematical analysis with the use of various teaching aids. In addition to the classic ones, which can be diversified by different ways of solving the same problem, modern software tools GeoGebra and Maxima contribute to a better understanding and formation of skills for the independent study of software material. With the use of GeoGebra and Maxima, a convenient environment is created for the organization and support of educational and cognitive activities, including educational research.
Keywords: means of activation; cognitive activity; mathematical analysis; GeoGebra; Maxima